Practicing Ballot Secrecy: Postal Voting and the Witness Requirement at the 2019 Finnish Elections - Weide, Marjukka (Frontiers in Political Science, 2021)
Electoral rights belong to the core of citizenship in democratic nation-states. Voting, then, represents an actualization of the relationship between the citizen and the political community. For citizens living outside the country in which they are eligible to vote, voting signifies a rare institutional connection to the country of origin. The aim of this article is to explore the introduction of the postal vote, a new form of voting for external voters at Finnish elections, from the grassroots perspective. The study focuses on how a central policy concern, safeguarding ballot secrecy, was resolved in the policy implementation by the witness requirement, and how the individual voters subsequently applied it. According to the voters’ accounts of the act of voting, the adopted method for underlining the importance of ballot secrecy in the Finnish overseas postal voting system, for many voters, makes little sense. While they effectively practice ballot secrecy, many fail to demonstrate this to the witnesses they were supposed to convince. Conversely, for these voters, the witness requirement merely works to break the secondary secrecy of elections, namely the secrecy of their participation itself. The empirical material for the article comprises policy documents and thematic text material (interviews, written responses) from 31 Finnish citizens living outside Finland. The article contributes to the scholarly debates on voting as a social, institutional and material practice. It further provides policy-relevant knowledge about grassroots implementation to various electoral administrations many of which, at the time of writing, face pressure to reform their repertoire of voting methods to function better in exceptional circumstances, such as a pandemic.